Multicomponent intervention for controlling hypertension in the adult rural population of Pakistan: a protocol for a hybrid type III implementation-effectiveness cluster randomised controlled trial - Catherine Hewitt; Aziz Sheikh; Simon Walker; Sajid Soofi; Kamran Siddiqi; Zulfiqar Ahmed Bhutta; Zainab Samad; Aysha Almas; Saima Afaq; Hajra Khwaja; Shiraz Hashmi; Imran Naeem; et al. (BMJ Open, 2025)
Introduction Though prior trials have shown the effectiveness of community-based hypertension detection and care delivery models, their adoption and translation to practice has been slow. In this study, we will develop and test strategies for the implementation and scale-up of a proven multicomponent hypertension intervention (MCHI) in Pakistan that comprises health education, blood pressure (BP) monitoring and referrals by lady health workers (LHWs) and hypertension management by physicians in primary care settings.Methods and analysis In this 24-month hybrid type III implementation-effectiveness cluster-randomised controlled trial, we will recruit 3000 adult hypertensive patients from two rural districts of Pakistan. We will engage public health sector managers, physicians and LHWs and use the Consolidated Framework for Implementation Research to identify barriers and facilitators to the implementation of an already proven-to-be-effective MCHI. Using Expert Recommendations for Implementing Change and the modified Delphi technique, a set of implementation strategies addressing barriers will be identified. The strategies will be categorised as level 1 (requiring a change in processes), level 2 (requiring a change in infrastructure) and level 3 (financial restructuring). Basic health units and 250–300 households from their catchment will be considered as clusters. Clusters will be randomised in a ratio of 1:1 to intervention and control. While MCHI will be offered in both trial arms (intervention and control), the aforementioned implementation strategies will be randomised to the intervention arm only, starting with level 1 and moving to levels 2 and 3 as needed. Baseline and 6-monthly follow-up surveys, each of 6 months duration, will be conducted to collect data from the recruited participants on sociodemographics, cardiovascular disease (CVD) risk factors, CVD-related expenses and quality of life. The primary outcome will be the mean difference in BP-lowering medications per participant between the intervention and control arms. The primary outcome will be analysed using a linear mixed model with fixed effects for baseline value of the outcome. Additional outcomes include implementation outcomes: proportion of LHWs conducting health education, BP screening and monitoring, facility referrals and proportion of physicians diagnosing and treating hypertensive patients; effectiveness outcomes: proportion of participants with controlled BP and improved EQ-5D-5L score.Ethics and dissemination Ethical approval has been obtained from the Ethics Review Committee of Aga Khan University Pakistan (ERC # 2023-9084-26739). Findings will be reported to: (1) study participants; (2) funding body and institutes collaborating and supporting the study; (3) provincial and district health departments to inform policy; (4) presented at local, national and international conferences and (5) disseminated by peer-review publicationsTrial registration number NCT06726057.